Novel basalt fiber winding yarn impregnating compound

The new basalt fiber wrapping yarn wetting agent prepared by using raw materials such as hydrolyzing coupling agents of specific ratios solves the problem of wetting agent technology blockade in basalt fiber production, improves the breaking strength and flame retardant performance of the fibers, and reduces production costs. , suitable for industrial applications.

CN119306408APending Publication Date: 2025-01-14四川文理学院
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310850423.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-12
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The technology blockade of wetting agents in basalt fiber production leads to high production costs, limiting the widespread application of basalt fibers, and having little knowledge of the research and proportion of wetting agents.

Method used

The new basalt fiber wound yarn wetting agent is prepared by raw materials such as hydrolyzing coupling agent, coupling agent, low-molecular film forming agent, polyethylene glycol 400 monooleate, ammonium acetate cationic surfactant and water-soluble epoxy resin. The basalt fibers are processed through specific ratios and process steps to improve their fracture strength, tensile strength and physical properties.

Benefits of technology

The treated basalt fibers have high fracture strength, tensile strength and flame retardant effects, low combustible content and moisture content, reasonable process and low cost, and are suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004333971490000021
    Figure BDA0004333971490000021
  • Figure BDA0004333971490000022
    Figure BDA0004333971490000022
  • Figure BDA0004333971490000023
    Figure BDA0004333971490000023
Patent Text Reader

Abstract

The invention discloses a novel basalt fiber winding yarn impregnating compound, belongs to the field of basalt fiber material preparation, and aims to further improve the components of the impregnating compound so as to meet the preparation requirements of basalt fibers with different performance requirements. The novel basalt fiber winding yarn impregnating compound is prepared from the following raw materials: a hydrolytic coupling agent, a coupling agent, a low-molecular film-forming agent, polyethylene glycol 400 monooleate, an ammonium acetate cationic surfactant, water-soluble epoxy resin and polyethylene glycol (400) monostearate. The basalt fiber treated by adopting the fiber winding yarn impregnating compound disclosed by the invention has relatively high breaking strength and tensile strength, and relatively low combustible matter content and water content. The basalt fiber prepared by adopting the preparation method is free of phenomena of filament scattering and agglomeration and balling, and has relatively good appearance and physical properties. The preparation method is reasonable in process, low in cost and good in effect, and has important significance on preparation and industrial production of the basalt fiber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of materials, in particular to the field of basalt fiber material preparation, and specifically to a novel basalt fiber winding yarn sizing agent. Background Art

[0002] Continuous basalt fiber is made of natural basalt ore, which is molten at a high temperature of about 1450℃ to 1500℃, formed by a platinum-rhodium alloy plate, and then drawn at high speed by a wire drawing machine to form a continuous non-metallic inorganic fiber. In the production process of continuous basalt fiber, almost no "three wastes" are generated, which has little pollution to the environment, and the product can be directly degraded in the environment after being discarded. It is called the pollution-free "green industrial raw material" in the 21st century. Continuous basalt fiber has excellent physical and chemical properties such as temperature resistance, single fiber mechanical strength, elastic modulus, density, creep rupture stress, chemical stability, etc. It has a wide range of uses in the fields of national defense and military industry, civil engineering, marine engineering, automobile and shipbuilding, aerospace, chemical fire protection, rail transportation, etc.

[0003] At present, although some progress has been made in the research on basalt, the overall research is still relatively scarce. Among them, the impregnating agent, as the "black box" in the basalt production industry, is a key factor in determining the fiber performance. However, foreign companies have adopted a technical blockade on the impregnating agent used for basalt, resulting in high production costs for basalt fibers, which limits the widespread application of basalt fibers. There are relatively few public reports on wetting agents used for basalt fibers, and reports on the raw materials and proportions of wetting agents are also rare.

[0004] To this end, the inventor has conducted a lot of research and obtained Chinese authorized patents for some basalt fiber sizing agents. However, it is still of great significance to further improve the sizing agent components to meet the preparation requirements of basalt fibers with different performance requirements. To this end, this application provides a new basalt fiber winding yarn sizing agent. Summary of the invention

[0005] The purpose of the present invention is to provide a new type of basalt fiber winding yarn impregnation agent in view of the above-mentioned problems. The basalt fiber treated with the basalt fiber winding yarn impregnation agent of the present application has higher breaking strength and tensile strength, and lower combustible content and moisture content. The basalt fiber prepared by the present application has no loose fibers and no clumping, and has better appearance and physical properties. The present application has a reasonable process, low cost and good effect, and is of great significance for the preparation and industrial production of basalt fiber.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] A novel basalt fiber winding yarn impregnation agent is prepared by using hydrolysis coupling agent, coupling agent, low molecular weight film-forming agent, polyethylene glycol 400 monooleate, ammonium acetate cationic surfactant, water-soluble epoxy resin, polyethylene glycol (400) monostearate as raw materials;

[0008] The coupling agent is γ-(2,3-epoxypropoxy)propyltrimethoxysilane, and the weight proportions of the raw materials are as follows:

[0009]

[0010] Or the coupling agent is 3-aminopropyltriethoxysilane, and the weight proportions of the raw materials are as follows:

[0011]

[0012] Or the coupling agent is 3-(isobutyleneoxy)propyltrimethoxysilane, and the weight proportions of the raw materials are as follows:

[0013]

[0014] Or the coupling agent is 3-(isobutyleneoxy)propyltrimethoxysilane, and the weight proportions of the raw materials are as follows:

[0015]

[0016]

[0017] The hydrolysis coupling agent is a weak acid.

[0018] The weak acid is acetic acid.

[0019] The low molecular weight film-forming agent is epoxy resin E-42 or epoxy resin E-44.

[0020] The water-soluble epoxy resin is one or more of sorbitol glycidyl ether, glycerol triglycidyl ether, and ethylene glycol diglycidyl ether.

[0021] The soft water is one or more of distilled water and deionized water.

[0022] The preparation method of the novel basalt fiber winding yarn sizing comprises the following steps:

[0023] (1) Weigh each component according to the ratio and set aside;

[0024] (2) dissolving the weighed coupling agent in soft water, adding a hydrolyzing coupling agent, adjusting the pH value of the solution to hydrolyze the coupling agent, and obtaining solution A;

[0025] (3) Add a low molecular weight film-forming agent, a water-soluble epoxy resin, polyethylene glycol 400 monooleate, an ammonium acetate cationic surfactant, and polyethylene glycol (400) monostearate to solution A respectively, and stir evenly to obtain a basalt wetting agent.

[0026] In response to the above problems, the present application provides a new type of basalt fiber winding yarn impregnation agent, which is prepared with hydrolytic coupling agent, coupling agent, low molecular weight film-forming agent, polyethylene glycol 400 monooleate, ammonium acetate cationic surfactant, water-soluble epoxy resin, polyethylene glycol (400) monostearate as raw materials according to a set ratio. In the present application, the CBNumber of polyethylene glycol 400 monooleate is: CB21149715, and the CAS of polyethylene glycol (400) monostearate is: 9004-99-3. In the present application, the weighed coupling agent is first dissolved in soft water, and then the hydrolytic coupling agent is added thereto to adjust the pH value of the solution, and the coupling agent is hydrolyzed in soft water by the hydrolytic coupling agent, and then solution A is obtained. Then, a low molecular weight film-forming agent, a water-soluble epoxy resin, polyethylene glycol 400 monooleate, an ammonium acetate cationic surfactant, and polyethylene glycol (400) monostearate were added to solution A respectively, and stirred evenly to obtain a basalt wetting agent.

[0027] In this application, weak acid is used as a hydrolysis coupling agent, γ-(2,3-epoxypropoxy)propyltrimethoxysilane is used as a coupling link, and soft water is used as a solvent. At the same time, low molecular weight epoxy resin E-42 or epoxy resin E-44, and water-soluble epoxy resin are used as film-forming agents; the water-soluble epoxy resin is used as a modified epoxy auxiliary film-forming agent, and polyol glycidyl ether (such as sorbitol glycidyl ether, glycerol triglycidyl ether, ethylene glycol diglycidyl ether, etc.) can be selected. This type of epoxy resin has an urethane group with high polarity and high chemical properties, and has strong adhesion and interface bonding ability to basalt fiber, so that the water-soluble epoxy resin can adhere to the surface of the basalt fiber, thereby achieving the purpose of enhancing the strength of the basalt fiber, and the water-soluble epoxy resin can improve the crack resistance of the basalt fiber and improve the physical properties of the basalt fiber.

[0028] Ammonium acetate cationic surfactant, polyethylene glycol 400 monooleate, and polyethylene glycol 400 monostearate are used as lubricants. Among them, polyethylene glycol 400 monostearate is a modified polyoxyethylene ester, which can play a good synergistic role when compounded with polyethylene glycol 400 monooleate.

[0029] The present application provides a universal winding yarn sizing agent for basalt fiber. When treating basalt fiber, the basalt fiber only needs to be immersed in the sizing agent. The basalt fiber treated by the present application has good breaking strength and tensile strength, low combustible content and water content, good flame retardant effect, good temperature resistance and chemical stability, high application value and broad application prospects. DETAILED DESCRIPTION

[0030] All features disclosed in this specification, or steps in all methods or processes disclosed, except mutually exclusive features and / or steps, can be combined in any manner.

[0031] Any feature disclosed in this specification, unless otherwise stated, can be replaced by other equivalent or alternative features with similar purposes. That is, unless otherwise stated, each feature is only an example of a series of equivalent or similar features.

[0032] In the embodiment of the present application, the infiltrant is prepared by a method comprising the following steps:

[0033] (1) Weigh each component according to the ratio and set aside;

[0034] (2) dissolving the weighed coupling agent in soft water, adding a hydrolyzing coupling agent, adjusting the pH value of the solution to hydrolyze the coupling agent, and obtaining solution A;

[0035] (3) Add a low molecular weight film-forming agent, a water-soluble epoxy resin, polyethylene glycol 400 monooleate, an ammonium acetate cationic surfactant, and polyethylene glycol (400) monostearate to solution A respectively, and stir evenly to obtain a basalt wetting agent.

[0036] In the examples of the present application, the treated basalt fiber samples were tested. Among them, the yarn breaking strength refers to the tensile breaking strength borne by the unit linear density of the sample, and the unit is Newton per tex (N / tex); the tensile strength refers to the ratio of the tensile breaking strength to the cross-sectional area of ​​the single filament, and the unit is megapascal (Mpa); the tensile modulus refers to the ratio of the stress difference to the corresponding strain difference, and the unit is megapascal (Mpa). The weak acid, silane, low molecular film-forming agent, polyethylene glycol 400 monooleate, ammonium acetate cationic surfactant, water-soluble epoxy resin, polyethylene glycol (400) monostearate are all commercially available products, and the soft water is prepared by the laboratory.

[0037] Example 1

[0038] The weight proportions of the raw materials of each component in this example are shown in Table 1 below.

[0039] Table 1 Group distribution ratio table of Example 1

[0040]

[0041] In Table 1, component 1 and ratio 1 are grouped together, and the corresponding components and ratios of a single solution are recorded as serial number 1; the others are recorded as serial numbers 2, 3, and 4 in the same way. At the same time, to simplify the table, the "+" in Table 1 indicates that the corresponding components are shown in the first column on the right side of Table 1.

[0042] The basalt fiber was treated with the sizing agent prepared in Example 1. The treatment results are shown in Table 2 below.

[0043] Table 2 Performance test results of each sample in Example 1

[0044]

[0045]

[0046] It has been determined that the basalt fiber was treated with the impregnating agent prepared in Example 1, and the maximum breaking strength of the obtained sample was 0.67N / Tex, the average value was 0.61N / Tex, the coefficient of variation was 5.36%, and the elongation at break was 3.79%; the maximum tensile strength of the sample was 3384Mpa, the average value was 2501Mpa, and the coefficient of variation was 17.07%; the elastic modulus of the sample reached 58939Mpa; the combustible content was about 0.81%; and the moisture content was about 0.016%.

[0047] Example 2

[0048] The weight proportions of the raw materials of each component in this example are shown in Table 3 below.

[0049] Table 3 Group distribution ratio table of Example 2

[0050]

[0051]

[0052] In Table 3, component 5 and ratio 5 are grouped together, and the corresponding components and ratios of a single solution are recorded as number 5; the others are recorded as number 6, number 7, and number 8 in the same way. At the same time, to simplify the table, "+" in Table 3 indicates that the corresponding components are shown in the first column on the right side of Table 3.

[0053] The basalt fiber was treated with the sizing agent prepared in Example 2. The treatment results are shown in Table 4 below.

[0054] Table 4 Performance test results of each sample in Example 2

[0055] No. 5 No. 6 No.7 No. 8 Breaking strength (N / Tex) 0.65 0.61 0.62 0.55 Elongation at break (%) 4.11 4.1 4.08 4.11 Tensile strength(Mpa) 3396.61 3395.81 3396.28 3396.02 Elastic modulus(Mpa) 69991.96 60226.25 61066.2 60220.8 Combustible content (%) 0.4838 0.4768 0.4654 0.4774 Moisture content (%) 0.0191 0.0179 0.0189 0.0186

[0056] It has been determined that the basalt fiber was treated with the wetting agent prepared in Example 2, and the maximum breaking strength of the obtained sample was 0.65N / Tex, the average value was 0.61N / Tex, the coefficient of variation was 3.99%, and the elongation at break was 4.11%; the maximum tensile strength of the sample was 3396Mpa, the average value was 2928Mpa, and the coefficient of variation was 12.56%; the elastic modulus of the sample reached 62876.24Mpa; the combustible content was about 0.48%; and the moisture content was about 0.019%.

[0057] Example 3

[0058] The weight proportions of the raw materials of each component in this example are shown in Table 5 below.

[0059] Table 5 Group distribution ratio table of Example 3

[0060]

[0061]

[0062] In Table 5, component 9 and ratio 9 are grouped together, and the corresponding components and ratios of a single solution are recorded as number 9; the others are recorded as number 10, number 11, and number 12 in the same way. At the same time, to simplify the table, the "+" in Table 5 indicates that the corresponding components are shown in the first column on the right side of Table 5.

[0063] The basalt fiber was treated with the sizing agent prepared in Example 3. The treatment results are shown in Table 6 below.

[0064] Table 6 Performance test results of each sample in Example 3

[0065] No. 9 No. 10 No. 11 No. 12 Breaking strength (N / Tex) 0.65 0.58 0.58 0.59 Elongation at break (%) 4.96 4.87 4.8 4.9 Tensile strength(Mpa) 3222.09 2768.1 2758.69 2564.87 Elastic modulus(Mpa) 68555.16 68225.09 68096.87 68136.1 Combustible content (%) 1.2058 1.2044 1.2039 1.2017 Moisture content (%) 0.0521 0.0524 0.0525 0.0498

[0066] It has been determined that the basalt fiber was treated with the impregnating agent prepared in Example 3, and the maximum breaking strength of the obtained sample was 0.65N / Tex, the average value was 0.58N / Tex, the coefficient of variation was 3.99%, and the elongation at break was 4.88%; the maximum tensile strength of the sample was 3222Mpa, the average value was 2828Mpa, and the coefficient of variation was 10.94%; the elastic modulus of the sample reached 68253.36Mpa; the combustible content was about 1.2%; and the moisture content was about 0.052%.

[0067] Example 4

[0068] The weight proportions of the raw materials of each component in this example are shown in Table 7 below.

[0069] Table 7 Group distribution ratio table of Example 4

[0070]

[0071] In Table 7, component 13 and ratio 13 are grouped together, and the corresponding components and ratios of a single solution are recorded as number 13; the others are recorded as number 14, number 15, and number 16. At the same time, to simplify the table, "+" in Table 7 indicates that the corresponding components are shown in the first column on the right side of Table 7.

[0072] The basalt fiber was treated with the sizing agent prepared in Example 4. The treatment results are shown in Table 8 below.

[0073] Table 8 Performance test results of each sample in Example 4

[0074]

[0075]

[0076] It has been determined that the basalt fiber was treated with the wetting agent prepared in Example 4, and the maximum breaking strength of the obtained sample was 0.61N / Tex, the average value was 0.57N / Tex, the coefficient of variation was 7.22%, and the elongation at break was 3.67%; the maximum tensile strength of the sample was 3460Mpa, the average value was 3038Mpa, and the coefficient of variation was 10.83%; the elastic modulus of the sample reached 68666.28Mpa; the combustible content was about 1.18%; and the moisture content was about 0.066%.

[0077] The present invention is not limited to the above-mentioned specific embodiments, but extends to any new features or any new combination disclosed in this specification, as well as any new method or process steps or any new combination disclosed.

Claims

1. A new type of basalt fiber winding yarn sizing agent, characterized in that: It is prepared by using hydrolysis coupling agent, coupling agent, low molecular weight film-forming agent, polyethylene glycol 400 monooleate, ammonium acetate cationic surfactant, water-soluble epoxy resin and polyethylene glycol (400) monostearate as raw materials; The coupling agent is γ-(2,3-epoxypropoxy)propyltrimethoxysilane, and the weight proportions of the raw materials are as follows: 3~5 parts of hydrolyzed coupling agent, 25~40 parts of coupling agent, 150~200 parts of low molecular weight film-forming agent, 10-30 parts of polyethylene glycol 400 monooleate, 10-25 parts of ammonium acetate cationic surfactant, 70~80 parts of water-soluble epoxy resin, 30-50 parts of polyethylene glycol (400) monostearate, Soft water 4000~6000 parts; Or the coupling agent is 3-aminopropyltriethoxysilane, and the weight proportions of the raw materials are as follows: 6~15 parts of hydrolysis coupling agent, 30~50 parts of coupling agent, 300~400 parts of low molecular weight film-forming agent, 15-30 parts of polyethylene glycol 400 monooleate, 10-50 parts of ammonium acetate cationic surfactant, 8~15 parts of water-soluble epoxy resin, 3-12 parts of polyethylene glycol (400) monostearate, Soft water 4000~6000 parts; Or the coupling agent is 3-(isobutyleneoxy)propyltrimethoxysilane, and the weight proportions of the raw materials are as follows: 1~6 parts of hydrolysis coupling agent, 20~50 parts of coupling agent, 350~400 parts of low molecular weight film-forming agent, 15-60 parts of polyethylene glycol 400 monooleate, 30-50 parts of ammonium acetate cationic surfactant, 80~160 parts of water-soluble epoxy resin, 40-50 parts of polyethylene glycol (400) monostearate, Soft water 4000~6000 parts; Or the coupling agent is 3-(isobutyleneoxy)propyltrimethoxysilane, and the weight proportions of the raw materials are as follows: 80~100 parts of hydrolysis coupling agent, 10~20 parts of coupling agent, 500~600 parts of low molecular weight film-forming agent, 150-200 parts of polyethylene glycol 400 monooleate, 100-250 parts of ammonium acetate cationic surfactant, 170~220 parts of water-soluble epoxy resin, 3-10 parts of polyethylene glycol (400) monostearate, 4000~6000 parts of soft water.

2. The wetting agent according to claim 1, characterized in that: The hydrolysis coupling agent is a weak acid.

3. The wetting agent according to claim 2, characterized in that: The weak acid is acetic acid.

4. The wetting agent according to any one of claims 1 to 3, characterized in that The low molecular weight film-forming agent is epoxy resin E-42 or epoxy resin E-44.

5. The wetting agent according to any one of claims 1 to 4, characterized in that The water-soluble epoxy resin is one or more of sorbitol glycidyl ether, glycerol triglycidyl ether, and ethylene glycol diglycidyl ether.

6. The wetting agent according to claim 1, characterized in that: The soft water is one or more of distilled water and deionized water.